A novel 3D MnNi2O4@MnNi2S4 core-shell nano array for ultra-high capacity electrode material for supercapacitors. (March 2022) - Lv, Xinrong; Feng, Li; Lin, Xiaoyun; Ni, Yongnian
Highlights: A novel 3D MnNi2 O4 @MnNi2 S4 core-shell nano array was firstly prepared via in-situ growth method. The MnNi2 O4 @MnNi2 S4 /NF exhibits excellent stability and ultra-high specific capacitance. The MnNi2 O4 @MnNi2 S4 /NF has a long cycling life. The MnNi2 O4 @MnNi2 S4 /NF based asymmetric supercapacitor also exihibits excellent rate performance. The MnNi2 O4 @MnNi2 S4 /NF is an outstanding electrode material for supercapacitors. Abstract: In this work, a novel 3D MnNi2 O4 @MnNi2 S4 core-shell nano array was successfully grown on nickel foam (NF) via in-situ growth method, which omitted the addition of binder and conductive additive and the complicated electrode preparation process. The MnNi2 O4 @MnNi2 S4 possesses a unique nanorod@nanosheet core-shell structure, which can provide abundant active sites near the electrode interface for rapid electrochemical reaction, so the MnNi2 O4 @MnNi2 S4 electrode materials exhibit high specific capacitance and excellent electrochemical properties. It is worth noting that the specific capacitance of the MnNi2 O4 @MnNi2 S4 reaches 3578.57 F g −1 at the current density of 1 A g −1, and 1009.52 F g −1 at the current density of 20 A g −1 . When the current density is 15 A g −1, the specific capacitance retention rate reaches 93.1% after 5000 cycles, showing good cycling performance. Moreover, the MnNi2 O4 @MnNi2 S4 //AC asymmetric device also exihibits low leakage current and excellent self-discharge characteristics. So, the MnNi2 O4 @MnNi2 S4 is an excellent electrode material for supercapacitors. Graphical abstract: Image, graphical abstract